METHOD AND MEANS OF INCREASING THE ENERGY EFFICIENCY OF COMPRESSED AIR PRODUCTION IN THE TECHNOLOGICAL PROCESS OF WOOD PROCESSING - FURSA, ANDRIY; MYKOLA, MOSHNORIZ (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Today, energy saving and energy efficiency are becoming more and more relevant and critical for modern enterprises, institutions and companies. Modern strategies in these areas are aimed at optimizing the use of energy resources and increasing the productivity of production processes. The high level of energy efficiency achieved is reflected in the competitiveness of products on world markets, thanks to the reduction of energy costs and the limitation of greenhouse gas emissions. Compressed air is an important resource for industry, often ranking fourth behind electricity, gas and water. The difference is that compressed air is produced on-site, giving consumers more control over its use and costs. However, the process of obtaining it requires significant energy costs. At enterprises in Europe and Australia, for example, compressor units that produce compressed air can use up to 10% of electricity, while in the United States this figure can reach 30%. Currently, the energy efficiency of the Ukrainian economy is twice as high as compared to world standards, which indicates inefficient use of heat, water and electricity. Therefore, it is important to understand that the implementation of measures for the energy efficiency of compressed air production is not only important from an ecological point of view, but also economically beneficial both for the country as a whole and for individual consumers. Increasing the level of energy efficiency of production processes, in particular wood processing, with the help of modern electrical engineering complexes, is a priority task for the industry. Thus, the analysis and development of energy-efficient solutions for the production of compressed air is a promising direction of development. This article provides an overview of well-known electrotechnical complexes that contribute to improving the energy efficiency of the technological process of wood processing.